Prospects and hot spots for mammalian target of rapamycin in the field of neuroscience from 2002 to 2021 - Li, Lijun; Xia, Xiaojing; Luo, Yunfeng; Zhu, Yuanting; Luo, Xuhong; Yang, Baolin; Shang, Lei (Frontiers in Integrative Neuroscience, 2022)
Mammalian target of rapamycin (mTOR) is an important molecule that regulates cell metabolism, growth, and proliferation in the nervous system. This study aimed to present the current study hot spots and predict the future development trend of the mTOR pathway in neurologic diseases using bibliometrics. We referred to the publications in the Web of Science Core Collection database. VOSviewer and CiteSpace programs were used to evaluate countries/regions, institutions, authors, journals, keywords, and citations showing the current study focus and predicting the future trend of mTOR in neuroscience. The search date ended on June 19, 2022, and there were 3,029 articles on mTOR in neuroscience from 2002 to 2021. Visual analysis showed that although the number of publications declined slightly in some years, the number of publications related to mTOR generally showed an upward trend, reaching its peak in 2021. It had the largest number of publications in the United States. Keywords and literature analysis showed that protein synthesis regulation, ischemia, mitochondrial dysfunction, oxidative stress, and neuroinflammation may be hot spots and future directions of the nervous system in mTOR studies. Recently, the most studied neurological diseases are Alzheimer’s disease, tuberous sclerosis complex, and depression, which are still worthy of further studies by researchers in the future. This can provide a useful reference for future researchers to study mTOR further in the field of neuroscience.